2021
DOI: 10.3390/rel12100840
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Values and Beliefs in Shaping Mental Health and Disorders

Abstract: Mental health is an area of continuous analysis, both in the context of understanding increasingly precise diagnostic criteria and the impact of therapeutic methods. In addition to these well-established directions of analysis and search, psychology tries to explore the factors that bring us closer to understanding the mechanisms of the genesis and development of disorders, as well as their importance in psychoeducation or therapy. The increased interest in issues of spirituality/religion observed in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
0
0
1
Order By: Relevance
“…For example, 93% of Indonesians consider religion important in their lives, whereas only 3% do in China (Pew Research Center, 2019). Some studies found that religiosity plays a key role in life satisfaction and meaning in life (Jung, 2018;Pastwa-Wojciechowska et al, 2021). Therefore, differences in religiosity might influence how Indonesian and Chinese emerging adults perceive the clarity of oneself and its implications for their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 93% of Indonesians consider religion important in their lives, whereas only 3% do in China (Pew Research Center, 2019). Some studies found that religiosity plays a key role in life satisfaction and meaning in life (Jung, 2018;Pastwa-Wojciechowska et al, 2021). Therefore, differences in religiosity might influence how Indonesian and Chinese emerging adults perceive the clarity of oneself and its implications for their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, se ha destacado que cuando la religión interactúa con enfermedades psiquiátricas, el nivel de gravedad de estas pudiera aumentar. En algunos de estos casos, la fe puede exacerbar o gatillar el sufrimiento en lugar de disminuirlo (Pastwa-Wojciechowska et al, 2021). Por ejemplo, Van-Ness (1999) indagó en los aspectos negativos y los positivos de las convicciones religiosas acerca de la salud física y salud mental; entre lo negativo mencionó el fanatismo, el ascetismo, las mortificaciones y el tradicionalismo opresivo, porque todas estas actitudes o creencias desfavorecen los procesos de autocuidado y de salud mental.…”
unclassified